Transportan Peptide Stimulates the Nanomaterial Internalization into Mammalian Cells in the Bystander Manner through Macropinocytosis - Yue-Xuan Li; Yushuang Wei; Rui Zhong; Ling Li; Hong-Bo Pang (MDPI AG, 2021)
Covalent coupling with cell-penetrating peptides (CPPs) has been a common strategy to facilitate the cell entry of nanomaterial and other macromolecules. Though efficient, this strategy requires chemical modifications on nanomaterials, which is not always desired for their applications. Recent studies on a few cationic CPPs have revealed that they can stimulate the cellular uptake of nanoparticles (NPs) simply via co-administration (bystander manner), which bypasses the requirement of chemical modification. In this study, we investigated the other classes of CPPs and discovered that transportan (TP) peptide, an amphiphilic CPP, also exhibited such bystander activities. When simply co-administered, TP peptide enabled the cells to engulf a variety of NPs, as well as common solute tracers, while these payloads had little or no ability to enter the cells by themselves. This result was validated in vitro and ex vivo, and TP peptide showed no physical interaction with co-administered NPs (bystander cargo). We further explored the cell entry mechanism for TP peptide and its bystander cargo, and showed that it was mediated by a receptor-dependent macropinocytosis process. Together, our findings improve the understanding of TP-assisted cell entry, and open up a new avenue to apply this peptide for nanomaterial delivery.